Substantiation and development of an optimal method of minimally invasive posterior interbody stabilization of vertebrae using distraction cages in patients with lumbar spondylolisthesis - Artem V. Stognii; Volodymyr O. Piatykop; Iurii O. Babalian (Ukrainian Neurosurgical Journal)
Objective to improve the effectiveness of treatment of patients with lumbar spondylolisthesis, the authors substantiated and developed a novel method of minimally invasive posterior interbody vertebral stabilization (MIPIVS) using distraction cages. Materials and methods: A clinical prospective comparative (controlled) single-center interventional cross-section study was conducted with a subsequent observation phase, as well as preliminary modeling and development of a noveltervention method. The biomechanical model was used to determine the possibility of restoring the functional state of the spine using distraction cages, and the stress-strain state of the structures was analyzed. The clinical part of the study involved 21 patients aged 35 to 68 (Me=56 [LQ=50; UQ=65]) years (15 women and 6 men), divided into three groups: the study group (n=4) treated with the author's method of MIPIVS (patent application No. a202302383 dated May 18, 2023), a comparison group (n=10) with the standard method of MIPIVS, a control group (n=7) treated with other methods of interbody spondylodesis. Patients were examined according to standard protocols. Logistic and statistical analyses were performed using standard nonparametric methods at a critical level of p<0.05. The principles of bioethics and biomedicine were observed. Results: Before and after surgical treatment of patients with degenerative spondylolisthesis of the lumbar spine, the size of the spinal canal was studied and the dynamics of neurological disorders was assessed. The authors developed a novel method of minimally invasive posterior interbody stabilization of vertebrae using distraction cages and determined the possibility of restoring the value of segmental lordosis, parameters of spinal-pelvic balance and sagittal contour of the spine as indicators of the functional state of the spine using a biomechanical model. The analysis also included assessment of the stress-strain state within the "transpedicular structure – spinal motion segment – distraction cage" system. Сonclusions: The proprietary method of MIPIVS using distraction cages, which has been substantiated and developed, will help to improve the effectiveness of treatment for patients with lumbar spondylolisthesis. Further research prospects include clinical testing of the author's MIPIVS method.